Vocational High School Students' Mathematical Problem-Solving Ability Viewed from Self Confidence - Gunawan Gunawan; Dinar Muflihati (AlphaMath : Journal of Mathematics Education, 2022)
Problem-solving ability is an essential cognitive aspect of Mathematics. One aspect of improving problem-solving is self-confidence. This study describes the mathematical problem-solving ability regarding the self-confidence of 34 students of class X TKRO 2 SMK Wiworotomo Purwokerto for the academic year 2019/2020. The method used is a descriptive qualitative, quantitative approach. The assessment instruments used include tests and self-confidence questionnaires. Students are grouped into low, medium, and high categories based on a self-confidence questionnaire. Each class was sampled using the purposive sampling technique. Data analysis includes reduction, presentation, and conclusion. The results obtained are high self-confidence, and students have good mathematical problem-solving skills, meaning that they fulfill all aspects of problem-solving. Students with medium self-confidence have good problem-solving skills but cannot provide conclusions at the end of the answer. Meanwhile, low self-confidence is not able to achieve indicators of problem-solving abilities. In addition, self-confidence and problem-solving ability have a positive correlation.